2021
DOI: 10.1093/humrep/deab130.679
|View full text |Cite
|
Sign up to set email alerts
|

P–680 Thyroid function in euthyroid women during controlled ovarian stimulation (COH): does the TSH fluctuations have an impact on IVF outcomes?

Abstract: Study question TSH blood levels play a role in terms of ovarian stimulation and pregnancy? Do we need to treat patients with TSH out of range? Summary answer Euthyroid patients with negative autoantibodies during COS should not be treated even if basal TSH is higher than 2.5 U/L What is known already Abnormal thyroid function is associated with adverse pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, the E2 levels on hCG trigger day of PCOS group is greater than that of non-PCOS group, and it is reported that the supraphysiological E2 levels during COH will also lead to the transient increase of TSH, this is mainly due to the increase of thyroxine binding protein caused by the super physiological high estrogen level in the serum, which reduces the concentration of free thyroid hormone and then causes the increase of serum TSH. Studies shown that the concentration of TSH increases with the increase of super physiological E2 level [29]. This may be another mechanism by which TSH affects oocyte maturation rate in PCOS group.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the E2 levels on hCG trigger day of PCOS group is greater than that of non-PCOS group, and it is reported that the supraphysiological E2 levels during COH will also lead to the transient increase of TSH, this is mainly due to the increase of thyroxine binding protein caused by the super physiological high estrogen level in the serum, which reduces the concentration of free thyroid hormone and then causes the increase of serum TSH. Studies shown that the concentration of TSH increases with the increase of super physiological E2 level [29]. This may be another mechanism by which TSH affects oocyte maturation rate in PCOS group.…”
Section: Discussionmentioning
confidence: 86%
“…In the current study, obese women with PCOS exhibited significantly higher TSH levels. Controlled ovarian hyperstimulation increased TSH levels in patients with adequate thyroid function, according to Noventa et al 2021 [43] . The authors hypothesized that regulated ovarian hyperstimulation would enhance thyroxine-binding protein due to elevated E2.…”
Section: Discussionmentioning
confidence: 96%
“…The authors hypothesized that regulated ovarian hyperstimulation would enhance thyroxine-binding protein due to elevated E2. This would lower free thyroid hormones and raise serum TSH (Noventa et al, 2021) [43] . Thus, we might infer that higher amounts of E2 in women with PCOS may influence thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…TSHRs are not only present on the surface of thyroid epithelial cells, but are also found on adipose tissue, fibroblasts, and reproductive tissues, including the ovaries and endometrium (4,14,16). TSH is critical for substance metabolism, folliculogenesis, ovine preimplantation embryo, placental formation, adverse pregnancy outcomes and neurological development (17)(18)(19). Hyperthyroidism and hypothyroidism during pregnancy have a well-established detrimental impact on menstrual irregularities (irregular or absent menstrual bleeding) and pregnancy complications, including pregnant and obstetric complications, adverse obstetric outcomes (19), and adverse neurological development of offspring (20).…”
Section: Discussionmentioning
confidence: 99%